Two models of inventory control with supplier selection in case of multiple sourcing: A case of Isfahan Steel Company - Masood Rabieh; Mohammad Ali Soukhakian; Ali Naghi Mosleh Shirazi (Journal of Industrial Engineering International, 2016)
Selecting the best suppliers is crucial for a company's success. Since competition is a determining factor nowadays, reducing cost and increasing quality of products are two key criteria for appropriate supplier selection. In the study, first the inventories of agglomeration plant of Isfahan Steel Company were categorized through VED and ABC methods. Then the models to supply two important kinds of raw materials (inventories) were developed, considering the following items: (1) the optimal consumption composite of the materials, (2) the total cost of logistics, (3) each supplier's terms and conditions, (4) the buyer's limitations and (5) the consumption behavior of the buyers. Among diverse developed and tested models-using the company's actual data within three pervious years-the two new innovative models of mixed-integer non-linear programming type were found to be most suitable. The results of solving two models by lingo software (based on company's data in this particular case) were equaled. Comparing the results of the new models to the actual performance of the company revealed 10.9 and 7.1 % reduction in total procurement costs of the company in two consecutive years.
Keywords: 650; Inventory control; Supplier selection; Multiple sourcing; Mathematical models